Anatomy of the back: surface and gross anatomy - Matthan, Joanna (Henry Stewart Talks, 2025)
Surface anatomy of the back, Surface landmarks of the back, Spine movements, Gross anatomy of the back, Organisation of the vertebral column, Spinal column -Vertebral column, Ligaments, Anatomy of a vertebra, Cervical region, Thoracic region, Lumbar region, Sacral and coccygeal regions, Features of individual vertebrae, Intervertebral discs